The interbranchial lymphoid tissue of Atlantic Salmon (Salmo salar L) extends as a diffuse mucosal lymphoid tissue throughout the trailing edge of the gill filament. (26th May 2015) - Dalum, Alf S.; Austbø, Lars; Bjørgen, Håvard; Skjødt, Karsten; Hordvik, Ivar; Hansen, Tom; Fjelldal, Per G.; Press, Charles McL; Griffiths, David J.; Koppang, Erling O.
ABSTRACT The teleost gill forms an extensive, semipermeable barrier that must tolerate intimate contact with the surrounding environment and be able to protect the body from external pathogens. The recent discovery of the interbranchial lymphoid tissue (ILT) has initiated an anatomical and functional investigation of the lymphoid tissue of the salmonid gill. In this article, sectioning of gill arches in all three primary planes revealed an elongation of the ILT outward along the trailing edge of the primary filament to the very distal end, a finding not previously described. This newly found lymphoid tissue was investigated using a range of morphological and transcriptional tools. Avoiding potential salinity‐related effects, the study focused on two fresh‐water life stages—smoltifying juveniles and mature adults. Aggregates of T‐cells continuous with the ILT were found within the thick epithelial lining of the trailing edge of the filament in considerably larger numbers than seen in the epithelium of the leading edge and of the interlamellar area. Only a few of these cells were identified as CD8α+‐cells, and there was a significantly (P < 0.05) higher relative expression of CD4‐ than of CD8‐ related genes in all gill segments investigated. Numerous major histocompatibility complex class II+‐cells were distributed uniformly throughout the filament epithelial tissue. Few Ig+‐cells were detected. Overall, the morphological features and comparable immune gene expression of the previously described ILT and the filament trailing edge lymphoid tissue suggest a close functional and anatomical relationship. We propose that the anatomical definition of the ILT must be broadened to include both the previously described ILT (to be renamed proximal ILT) and the trailing edge lymphoid tissue (to be named distal ILT). This extended anatomical localisation identifies the ILT as a widely distributed mucosal lymphoid tissue in the gill of Atlantic salmon. J. Morphol. 276:1075–1088, 2015. © 2015 Wiley Periodicals, Inc.